The Zero Emissions Commitment and climate stabilization - Palazzo Corner, Sofia; Siegert, Martin; Ceppi, Paulo; Fox-Kemper, Baylor; Frölicher, Thomas L.; Gallego-Sala, Angela; Haigh, Joanna; Hegerl, Gabriele C.; Jones, Chris D.; Knutti, Reto; Koven, Charles D.; MacDougall, Andrew H.; et al. (Frontiers in Science, 2023)
How do we halt global warming? Reaching net zero carbon dioxide (CO 2 ) emissions is understood to be a key milestone on the path to a safer planet. But how confident are we that when we stop carbon emissions, we also stop warming? The Zero Emissions Commitment (ZEC) quantifies how much warming or cooling we can expect following a complete cessation of anthropogenic CO 2 emissions. To date, the best estimate by the IPCC Sixth Assessment Report is zero change, though with substantial uncertainty. In this article, we overview the changes expected in major Earth system processes after net zero and their potential impact on global surface temperature, providing an outlook toward building a more confident assessment of ZEC in the decades to come. We propose a structure to guide research into ZEC and associated changes in the climate, separating impacts expected over decades, centuries and millennia. As we look ahead at the century billed to mark the end of net anthropogenic CO 2 emissions, we ask: what is the prospect of a stable climate in a post-net zero world?